Digitalization of potato breeding program: Improving data collection and management. Issue 1 (January 2023) - Dipta, Bhawna; Sood, Salej; Devi, Rasna; Bhardwaj, Vinay; Mangal, Vikas; Thakur, Ajay Kumar; Kumar, Vinod; Pandey, N.K.; Rathore, Abhishek; Singh, A.K.
Abstract: A plant breeding program involves hundreds of experiments, each having number of entries, genealogy information, linked experimental design, lists of treatments, observed traits, and data analysis. The traditional method of arranging breeding program information and data recording and maintenance is not centralized and is always scattered in different file systems which is inconvenient for retrieving breeding information resulting in poor data management and the loss of crucial data. Data administration requires a significant amount of manpower and resources to maintain nurseries, trials, germplasm lines, and pedigree records. Further, data transcription in scattered spreadsheets and files leads to nomenclature and typing mistakes, which affects data analysis and selection decisions in breeding programs. The accurate data recording and management tools could improve the efficiency of breeding programs. Recent interventions in data management using computer-based breeding databases and informatics applications and tools have made the breeder's life easier. Because of its digital nature, the data obtained is improved even further, allowing for the acquisition of images, voice recording and other specific data kinds. Public breeding programs are far behind the industry in the use of data management tools and softwares. In this article, we have compiled the information on available data recording tools and breeding data management softwares with major emphasis on potato breeding data management.